Structural filters for monetary analysis: the inflationary movements of money in the euro area - Annick Bruggeman; Gonzalo Camba-Méndez; Björn Fischer; Jo\~ao Sousa (European Central Bank (ECB), 2005)
The quantity theory of money predicts a positive relationship between monetary growth and inflation over long-run horizons. However, in the short-run, transitory shocks to either money or inflation can obscure the inflationary signal stemming from money. The spectral analysis of time series provides filtering tools for removing fluctuations associated with certain frequency movements. However, use of these techniques in isolation is often criticised as being an oversimplistic statistical exercise potentially void of economic content. The objective of this paper is to develop `structural' filtering techniques that rely on the use of spectral analysis in combination with a structural economic model with well identified shocks. A `money augmented' Phillips curve that links inflation to money tightness and demand shocks of medium to long-term persistence is presented. It is shown that medium to long-term movements in inflation are mostly associated with the estimated monetary indicators.
Keywords: E31; E50; C32; 330; Inflation and Money; Inflation; Geldmenge; Prognose; Eurozone; EU-Staaten; ARMA-Modell